KAJIAN OPTIMASI PROSES PENGOLAHAN PRODUK BERAS INSTAN UBI JALAR (Ipomoea batata L.) VARIETAS SHIROYUTAKA - Nurbani Kalsum; Beni Hidayat; Surfiana Surfiana (Jurnal Teknologi & Industri Hasil Pertanian, 2008)
The objective of this research was to optimize the product of Shiroyutaka sweet potato instant rice processing.  This research was done in three steps of optimation process.  The first step was the addition of water with the ratio of 1:1.5, 1:2, and 1:3, the second step was the temperature of added water, and the third step was the binder compound addition (0, 5, and 10%).  The results indicated that the optimal characteristic of instant rice was obtained by addition of 5% tapioca, addition of hot water to form a dough, forming, cooking in rice cooker until it gets cooked, drying in the form of plate, and milling. The product had the composition of 6.68% water, 82,78% of total carbohydrate, 1,73% of  protein, 1,38% of fat, 5,84% of fiber, and 1,59% of ash. This product required 5 minute preparation and consumer acceptable score of 3.80. Keywords:  Instant rice, sweet potato, Shiroyutaka